2017
DOI: 10.1111/tri.13016
|View full text |Cite
|
Sign up to set email alerts
|

Toward a conditional approach to anonymity? An explorative multicenter longitudinal study among anonymous living kidney donors and recipients

Abstract: Anonymity between living donors and recipients is a topic of discussion among transplant professionals. This longitudinal study explored living kidney donors' and patients' perspectives on anonymity. Prior to surgery (T0) and 3 months afterward (T1), participants in unspecified or specified indirect donation programs completed a questionnaire on their experiences with and attitudes toward anonymity as well as demographic and medical characteristics. Nonparametric tests were used to assess group differences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 12 publications
5
16
0
1
Order By: Relevance
“…36 In The Netherlands and Sweden, where absolute anonymity is maintained long-term, 2 studies found that the majority were comfortable with having had anonymity maintained; however, the majority felt that if both donor and recipient wanted to meet after the transplant, it should be allowed. 36 In The Netherlands and Sweden, where absolute anonymity is maintained long-term, 2 studies found that the majority were comfortable with having had anonymity maintained; however, the majority felt that if both donor and recipient wanted to meet after the transplant, it should be allowed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 In The Netherlands and Sweden, where absolute anonymity is maintained long-term, 2 studies found that the majority were comfortable with having had anonymity maintained; however, the majority felt that if both donor and recipient wanted to meet after the transplant, it should be allowed. 36 In The Netherlands and Sweden, where absolute anonymity is maintained long-term, 2 studies found that the majority were comfortable with having had anonymity maintained; however, the majority felt that if both donor and recipient wanted to meet after the transplant, it should be allowed.…”
Section: Discussionmentioning
confidence: 99%
“…Policies regarding long-term NDD/recipient anonymity differ among countries. 36 In The Netherlands and Sweden, where absolute anonymity is maintained long-term, 2 studies found that the majority were comfortable with having had anonymity maintained; however, the majority felt that if both donor and recipient wanted to meet after the transplant, it should be allowed. 7,36 As noted above, we maintain anonymity for 6 months as a "protection" for both donor and recipient to physically recover.…”
Section: Massey Et Al Found That Ndds Valued Benevolence Independencementioning
confidence: 99%
See 1 more Smart Citation
“…Conditional approach[ 38 ]: When the donor-recipient pairs give consent for meeting after surgery, they are allowed to meet each other after surgery in some countries such as the United States of America[ 39 ] and the United Kingdom[ 40 ]. In other countries, such as the Netherlands and Sweden[ 41 ], anonymity is absolute.…”
Section: Pros and Cons Of Anonymity In Developed World And (Non-) Anomentioning
confidence: 99%
“…An Ethical, Legal and Psychosocial Aspects of Organ Transplantation (ELPAT), a subsection of the European Society for Organ Transplantation reported that a conditional approach to anonymity should be possible after surgery[ 42 ]. Pronk et al[ 38 ] showed that most donor-recipient pairs who participated in anonymous donation process are in favour of a conditional approach to anonymity. Guidelines on how to revoke anonymity if both parties agree are needed and should include education about pros and cons of (non-) anonymity and a logistical plan on how, when, where, and by whom anonymity should be revoked.…”
Section: Pros and Cons Of Anonymity In Developed World And (Non-) Anomentioning
confidence: 99%